1998
DOI: 10.1111/j.1553-2712.1998.tb02808.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraarterial vs Intravenous Administration of Antivenin for the Treatment of Crotalide atrox Antivenin for the Treatment of Crotalidae atrox Envenomation: A Pilot Study

Abstract: i.a. antivenin results in a modest but significant decrease in tissue edema when compared with i.v..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Pigs have been used successfully in previous envenomation research. 8,9 According to previous research, 8 the mortality in control pigs treated with C atrox venom at 20 mg/kg was estimated to be 100%. We were unable to perform a sample size calculation because of the absence of baseline data on time to mortality and compartment pressures.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
See 1 more Smart Citation
“…Pigs have been used successfully in previous envenomation research. 8,9 According to previous research, 8 the mortality in control pigs treated with C atrox venom at 20 mg/kg was estimated to be 100%. We were unable to perform a sample size calculation because of the absence of baseline data on time to mortality and compartment pressures.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…[8][9][10][11][12] Additionally, we believed that the pig was the best animal model to simulate the human response to envenomation under the conditions of our experiment. Pigs have been used successfully in previous envenomation research.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…A porcine model was chosen by considerations of availability, cost, acceptability to the institutional animal review committee for experimental study, the expectation that venom toxicity is similar to that seen in humans, and literature supporting its use. [35][36][37][38] The university animal care use committee approved the study. Subjects were 12 pigs ranging from 9.1 kg to 11.4 kg.…”
Section: Methodsmentioning
confidence: 99%
“…Although some authors have attempted to find ways to maximize antivenom exposure to venom components at the bite site in the hopes of limiting necrosis, none, to our knowledge, have met with significant success to date. Bania et al 22 studied intra-arterial administration of ACP in a porcine model of rattlesnake venom poisoning and found a ''modest'' reduction in soft tissue swelling, but they did not measure or evaluate necrosis. McCollough and Gennaro 23 used radiolabeled antivenom in a dog model that compared intravenous (IV), intramuscular (IM), and subcutaneous (SQ) administration and found that more antivenom got to the venom injection site by the IV route (84.9% compared to 1.43% and 5.6%, respectively).…”
Section: Introductionmentioning
confidence: 99%